ANALISIS JIWA KEWIRAUSAHAAN PEMIMPIN, GAYA PARTISIPASI PARA ANGGOTA, DAN MODEL MANAJEMEN KOPERASI DALAM MENINGKATKAN KINERJA KOPERASI DI KOTA SEMARANG - Heru Sri Wulan (Universitas Pandanaran, 2015)
Data on Cooperative business growth shows that the performance of cooperatives indicated by business volume and net income suffer a declineduring 2008-2010. Various previous studies make the point that factors affecting fruitful business performance are entrepreneurship, member participation, and cooperative management. Based on the empirical phenomena found in the fieldof this research, the research problem formulated here is “How to improve theperformance of Various Business Cooperatives in Semarang?”To answer the research problem, we use an approach with three research variable, i.e., entrepreneurship, member participation, and cooperative management. The test of the influence of each variable is conducted using Multiple Regression Test on a data collection which was obtained through interviews using questionnaire with 74 managers of cooperatives in Semarang.The result of the regression test over the research variable found that entrepreneurship significantly influence on performance of Various Business Cooperatives in Semarang, member participation significantly influence performance of Various Business Cooperatives in Semarang, and cooperative management significantly influence performance of Various Business Cooperatives in Semarang.Keyword : Entrepreneurship, member participation, and cooperative management, performance